PENGARUH PENDAPATAN ASLI DAERAH DAN DANA TRANSFER TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH (Studi Kasus Pada Pemerintah Kabupaten dan Kota Di Jawa Tengah Tahun 2018-2023) - Zalza Putri Maharani; Haryanto Haryanto (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the influence of Regional Original Revenue (PAD) and transfer funds on the level of regional financial independence in districts and cities in Central Java during the 2018-2023 period. Regional financial independence is an important indicator in assessing the ability of a region to finance government and development activities without relying on assistance from the central government. The method used in this study is regression analysis with panel data covering 29 districts and 6 cities in Central Java.The results of the study show that PAD has a positive and significant influence on the level of regional financial independence, which indicates that increasing PAD will contribute to increasing financial independence. In contrast, transfer funds from the central government show a negative influence on regional financial independence, indicating that reliance on transfer funds can reduce regional incentives to increase PAD. In addition, there are significant differences in the level of financial independence between districts and cities, which are influenced by factors such as the potential of regional resources and the fiscal policies implemented.Based on these findings, it is suggested that local governments focus more on developing PAD sources and reducing dependence on transfer funds. Policies that support regional capacity building in managing and utilizing local resources are indispensable to achieve better financial independence. This research is expected to contribute to more effective policy making in regional financial management in Central Java.